SYSTEMATIC WASTE MANAGEMENT FOR EMPOWERMENT OF AMBULU VILLAGE COMMUNITY - Amirudin; Deviari Damalita (International Journal of Management, Economic, Business and Accounting, 2022)
Waste is something that is always present in our daily lives. All the activities will inevitably result in the waste and so is going on in the village of Ambulu, District of Losari, Cirebon. The problem of this research is the process of waste management, which can’t be categorised as good because the process is done by discharge management is not in the appropriate place and dispoce it using the combustion process. The purpose of this study was to determine the existing waste management system in the village of Ambulu, District of Losari,Cirebon. The method used on this research is a qualitative study design with observational descriptive. It conducted by field surveys, focus group discussions with participant, open inteviews, and literature study. Participants used in this study is representative of the Environment Agency, the village head, village councils, youth clubs and organizations in the village. The study states that waste management still in the unfavorable category, this is due to many factors : the lack of land for the contruction of temporary shelters, facilities and infrastructures are not good enough and the level of public awareness is still low about the importance to manage waste properly. The advice can be given is to socialize, to schedule regular clean up to clen the village and create a budget for land acquisition, which will be used for temporary shelter.